Immunization with a Chimera Consisting of the B Subunit of Shiga Toxin Type 2 and Brucella Lumazine Synthase Confers Total Protection against Shiga Toxins in Mice. - Mejias, Maria Pilar (2013)
The striking feature of enterohemorrhagic Escherichia coli (EHEC) infections is the production of Shiga toxins (Stx) implicated in the development of the life-threatening hemolytic uremic syndrome. Despite the magnitude of the social impact of EHEC infections, no licensed vaccine or effective therapy is available for human use. One of the biggest challenges is to develop an effective and safe immunogen to ensure nontoxicity, as well as a strong input to the immune system to induce long-lasting, high-affinity Abs with anti-Stx–neutralizing capacity. The enzyme lumazine synthase from Brucella spp. (BLS) is a highly stable dimer of pentamers and a scaffold with enormous plasticity on which to display foreign Ags. Taking into account the advantages of BLS and the potential capacity of the B subunit of Stx2 to induce Abs that prevent Stx2 toxicity by blocking its entrance into the host cells, we engineered a new immunogen by inserting the B subunit of Stx2 at the amino termini of BLS. The resulting chimera demonstrated a strong capacity to induce a long-lasting humoral immune response in mice. The chimera induced Abs with high neutralizing capacity for Stx2 and its variants. Moreover, immunized mice were completely protected against i.v. Stx2 challenge, and weaned mice receiving an oral challenge with EHEC were completely protected by the transference of immune sera. We conclude that this novel immunogen represents a promising candidate for vaccine or Ab development with preventive or therapeutic ends, for use in hemolytic uremic syndrome–endemic areas or during future outbreaks caused by pathogenic strains of Stx-producing E. coli.